V5: Coordination and Change - Andah, Winston; Biney, Charles (2010)
The Coordination Project V5 will ensure coherence amongst the other 4 Volta BDC Projects, manage their interdependence and data protocols in such a way to allow smooth running of the program and also monitor and evaluate the quality of research outputs. Through communication strategies to be developed, V5 will assist in linking projects with policy makers and other stakeholders to create opportunities that will enrich the research process and subsequently the uptake of research outputs